The coming golden age : 31 ways to be kingdom ready - Jeremiah, David, 1941- (W Publishing Group, 2024)
Most days peace feels elusive, and our hope feels light-years away. And it is almost impossible to set our minds on God's coming reign. But what if the return of the King and His Kingdom is exactly what we need to find our peace and ground our hope today? His coming victorious reign is what gives us the strength we need now.